(S)-[18F]THK5117 brain uptake is associated with Aβ plaques and MAO-B enzyme in a mouse model of Alzheimer's disease - Alzghool Obada M; Rokka Johanna; López-Picón Francisco R; Snellman Anniina; Helin Jatta S; Okamura Nobuyuki; Solin Olof; Rinne Juha O; Haaparanta-Solin Merja (United Kingdom, 2022)
The mouse model of beta-amyloid (Aβ) deposition, APP/PS1-21, exhibits high brain uptake of the tau-tracer (S)-[18F]THK5117, although no neurofibrillary tangles are present in this mouse model. For this reason we investigated (S)-[18F]THK5117 off-target binding to Aβ plaques and MAO-B enzyme in APP/PS1-21 transgenic (TG) mouse model of Aβ deposition. APP/PS1-21 TG and wild-type (WT) control mice in four different age groups (2-26 months) were imaged antemortem by positron emission tomography with (S)-[18F]THK5117, and then brain autoradiography. Additional animals were used for immunohistochemical staining and MAO-B enzyme blocking study with deprenyl pre-treatment. Regional standardized uptake value ratios for the cerebellum revealed a significant temporal increase in (S)-[18F]THK5117 uptake in aged TG, but not WT, brain. Immunohistochemical staining revealed a similar increase in Aβ plaques but not endogenous hyper-phosphorylated tau or MAO-B enzyme, and ex vivo autography showed that uptake of (S)-[18F]THK5117 co-localized with the amyloid pathology. Deprenyl hydrochloride pre-treatment reduced the binding of (S)-[18F]THK5117 in the neocortex, hippocampus, and thalamus. This study's findings suggest that increased (S)-[18F]THK5117 binding in aging APP/PS1-21 TG mice is mainly due to increasing Aβ deposition, and to a lesser extent binding to MAO-B enzyme, but not hyper-phosphorylated tau.